The pathogenesis of idiopathic normal pressure hydrocephalus based on the understanding of AQP1 and AQP4 - Zitong Zhao; Zitong Zhao; Zitong Zhao; Jian He; Yibing Chen; Yibing Chen; Yibing Chen; Yuchang Wang; Yuchang Wang; Yuchang Wang; Chuansen Wang; Chuansen Wang; et al. (Frontiers in Molecular Neuroscience, 2022)
Idiopathic normal pressure hydrocephalus (iNPH) is a neurological disorder without a recognized cause. Aquaporins (AQPs) are transmembrane channels that carry water through cell membranes and are critical for cerebrospinal fluid circulation and cerebral water balance. The function of AQPs in developing and maintaining hydrocephalus should be studied in greater detail as a possible diagnostic and therapeutic tool. Recent research indicates that patients with iNPH exhibited high levels of aquaporin 1 and low levels of aquaporin 4 expression, suggesting that these AQPs are essential in iNPH pathogenesis. To determine the source of iNPH and diagnose and treat it, it is necessary to examine and appreciate their function in the genesis and maintenance of hydrocephalus. The expression, function, and regulation of AQPs in iNPH are reviewed in this article, in order to provide fresh targets and suggestions for future research.